Typography sketchbooks. - Heller, Steven, 1950-; Talarico, Lita, ....- (London : Thames and Hudson, 2011)
Selected by the world's most knowledgeable and well-connected graphic-design commentator, Steven Heller, this survey gets into the minds of designers who create typefaces, word-images and logos through their private sketchbooks. Nearly 120 of the world's leading typographers and graphic designers open up their private sketchbooks to reveal their creative processes. Aimed at all those who use type, whether by hand or on screen, and selected by the world's most knowledgeable and well-connected graphic design commentator, Steven Heller, this survey gets into the minds of designers who create typefaces, word-images and logos through their private sketchbooks. Arranged by designer, this collection reveals how the world's top typographers and designers strive to find new and exciting ways of communicating through letters and words. Contributors include both the world-renowned - Milton Glaser, Erik Spiekermann, Peter Bilak and Jean Baptiste Levée - and the up and coming, while Steven Heller and Lita Talarico's text provides invaluable commentary on the designers' creative process, their design philosophies, inspirations, techniques and influences.
Keywords: Grafische kunst; Grafische technieken; Grafische vormgeving; Letters; Typografie